A DESCRIPTIVE STUDY VALIDITY OF LOCALING ENGLISH TEST OF THE FIRST YEAR USED AT SMP MUHAMMADIYAH SURUHSALATIGA 2009/2010 ACADEMIC YEAR - MUFLIKHATI, YULIYA (2011)
The objectives of research are to describe the types of the test item that are used at SMP Muhammadiyah Suruh and to describe whether the test item used at SMP Muhammadiyah Suruh match competencies which want to be measured in the syllabus. The writer uses observation and document as the instruments to collect the data needed. She also analyzes the document of the teacher made test items by identifying the type of test that has been developed through the written test items. The writer applies descriptive qualitative method. The steps of data analysis, the writer coverage of the language skill, material content and curriculum and to describe the technique of the test. The result of the study shows that the types and techniques of localing English test given in SMP Muhammadiyah Suruh using language testing principles has appropriateness. The appropriateness is the teacher can be active in developing some techniques of the test in language skills (reading, speaking, listening, and writing), and the teacher can improve some variations of test based on the language testing principles and the result of the identifications about the test content is good because it matches with the educational objectives in the syllabus.